The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1124/jpet.120.000152
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Dilates and Counteracts Ethanol-Induced Constriction of Cerebral Arteries

Abstract: The increasing recognition of the role played by cerebral artery dysfunction in brain disorders has fueled the search for new cerebrovascular dilators. Celastrol, a natural triterpene undergoing clinical trials for treating obesity, exerts neuroprotection, which was linked to its antioxidant/anti-inflammatory activities. We previously showed that celastrol fitted pharmacophore criteria for activating calcium-and voltage-gated potassium channels of large conductance ("BK") made of subunits cloned from cerebrova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 80 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Indeed, KCNMB1 −/− mice exhibited a significant reduction in ethanol-induced inhibition of BK-induced STOCs and its resulting vasoconstriction ( 125 ). These results identified the BK β 1 subunit as a possible therapeutic target to counteract alcohol-induced inhibition of SM BK channels and its associated cerebrovascular constriction, a proof-of-principle being obtained both in vitro and in vivo data with celastrol, a neuroprotective agent ( 145 ).…”
Section: Muscle Types and Their Mechanisms For Contractionmentioning
confidence: 74%
“…Indeed, KCNMB1 −/− mice exhibited a significant reduction in ethanol-induced inhibition of BK-induced STOCs and its resulting vasoconstriction ( 125 ). These results identified the BK β 1 subunit as a possible therapeutic target to counteract alcohol-induced inhibition of SM BK channels and its associated cerebrovascular constriction, a proof-of-principle being obtained both in vitro and in vivo data with celastrol, a neuroprotective agent ( 145 ).…”
Section: Muscle Types and Their Mechanisms For Contractionmentioning
confidence: 74%
“…Outputs of current investigations showcased that CL treatment ameliorated AIS-induced BI by inhibiting microglial injury and Nrf2/HO-1 pathway activations. Previous investigations advised that celastrol can be used as novel drug to cause cerebral vascular dilation in cases where endothelial and/or BK channel function is impaired [ 33 ]. But if CL treatment can improve the vascular system after acute ischemic stroke is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang, Chen, et al, 2020). Triterpene 204 also revealed an antiinflammatory potential in inhibiting disorders such as rheumatoid arthritis (Xinqiang et al, 2020), mast cell-mediated allergic diseases (Zhu et al, 2021), as well as the prevention and reversal of ethanolinduced constriction in brain arteries (North et al, 2020). Recently, Q.…”
Section: Friedelanes-compounds 198-204mentioning
confidence: 99%
“…Commonly isolated from the species Tripterygium wilfordii , celastrol was investigated for its protective action against chondrocyte apoptosis, promoting autophagy and inhibiting the NF‐κB signaling pathway in vitro and in vivo (Feng et al, 2020) In addition, this compound exhibits antiinflammatory properties in murine macrophages treated with LPS, exerting antifibrotic effects in a model with bleomycin‐induced systemic sclerosis (X. Jiang, Chen, et al, 2020). Triterpene 204 also revealed an antiinflammatory potential in inhibiting disorders such as rheumatoid arthritis (Xinqiang et al, 2020), mast cell‐mediated allergic diseases (Zhu et al, 2021), as well as the prevention and reversal of ethanol‐induced constriction in brain arteries (North et al, 2020). Recently, Q. Zhao, Tang et al (2020) reported a new role for celastrol ( 204 ) in protecting against acute liver injury, through the modulation of peroxisome proliferator‐activated receptor‐α (PPARα) signaling.…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%